Liquid Chromatography/Tandem Mass Spectrometry Method for Quantitation of Cremophor EL and Its Applications - V. Vijaya Bhaskar (International Journal of Analytical Chemistry, 2013)
A rapid sensitive and selective MRM based method for the determination of Cremophor EL (CrEL) in rat plasma was developed using liquid chromatography/tandem mass spectrometry (LC-MS/MS). CrEL and polypropylene glycol (internal standard) were extracted from rat plasma with acetonitrile and analysed on C18 column (XBridge, 50 × 4.6 mm, 3.5 μm). The most abundant molecular ions corresponding to PEG oligomers at m/z 828, 872, 916 and 960 with daughter ion at m/z 89 were selected for multiple reaction monitoring (MRM) in electrospray mode of ionisation. Plasma concentrations of CrEL were quantified after administration through oral and intravenous routes in male sprague dawley rats at a dose of 0.26 g/kg. The standard curve was linear (0.9972) over the concentration range of 1.00 to 200 μg/mL. The lower limit of quantitation for CrEL was 1.00 μg/mL using 50 μL plasma. The coefficient of variation and relative error for inter and intra assay at three QC levels were 0.69 to 9.21 and −7.60 to 4.74 respectively. A novel proposal was conveyed to the scientific community, where formulation excipient can be analysed as qualifier in the analysis of NCEs to address the spiky plasma concentration profiles.